Contextuality of Mathematical Beliefs and Reasoning - Merighi, Caroline. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Education.; Advisor: Barbara Brizuela.; Committee: David Hammer, Kim Ruane, and Michelle Wilkerson.; Keywords: Mathematics education, Science education, and Teacher education.